The Influence of Prior Relationship on Perceptions of Stalking: A Comparison of Laypersons, Nonspecialist Police Officers, and Specialist Police Officers - Scott, A.; Nixon, K.; Sheridan, Lorraine (Sage Publications, Inc., 2013)
The current research examined the influence of prior relationship on perceptions of stalking, and compared the perceptions of laypersons, nonspecialist police officers, and specialist police officers. Two studies employed experimental designs where participants were presented with one of three vignettes in which the nature of the prior relationship was manipulated so that the perpetrator and victim were portrayed as strangers, acquaintances, or ex-partners. Participants comprised 101 nonspecialist police officers and 108 laypersons in Study 1, and 49 specialist police officers and 49 nonspecialist police officers in Study 2. Findings indicate that nonspecialist police officers and laypersons shared the common misperception that stranger stalkers present a greater threat to the personal safety of their victims than acquaintance or ex-partner stalkers. Specialist police officers were less susceptible to common misperceptions and believed that intervention was more necessary. Specialist police officers also believed that the perpetrator’s behavior would cause the victim more alarm or personal distress than nonspecialist police officers.